Tính đạo hàm hàm số :
\(y=\frac{4^x-1}{6^x}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(g'\left( x \right) = y' = {\left( {2x + \frac{\pi }{4}} \right)^,}.\cos \left( {2x + \frac{\pi }{4}} \right) = 2\cos \left( {2x + \frac{\pi }{4}} \right)\)
b) \(g'\left( x \right) = - 2{\left( {2x + \frac{\pi }{4}} \right)^,}.\sin \left( {2x + \frac{\pi }{4}} \right) = - 4\sin \left( {2x + \frac{\pi }{4}} \right)\)
Ta có: \(y' = {\left( {\tan x} \right)^\prime } = \frac{1}{{{{\cos }^2}x}}\)
Vậy \(y'\left( {\frac{{3\pi }}{4}} \right) = \frac{1}{{{{\cos }^2}\left( {\frac{{3\pi }}{4}} \right)}} = 2\).
a, \(y=3x^4-7x^3+3x^2+1\)
\(y'=12x^3-21x^2+6x\)
b, \(y=\left(x^2-x\right)^3\)
\(y'=3\left(x^2-x\right)^2\left(2x-1\right)\)
c, \(y=\dfrac{4x-1}{2x+1}\)
\(y'=\dfrac{4+2}{\left(2x+1\right)^2}\)
\(y'=\dfrac{6}{\left(2x+1\right)^2}\)
a: y=3x^4-7x^3+3x^2+1
=>y'=3*4x^3-7*3x^2+3*2x
=12x^3-21x^2+6x
b: \(y'=\left[\left(x^2-x\right)^3\right]'\)
\(=3\left(2x-1\right)\left(x^2-x\right)^2\)
c: \(y'=\dfrac{\left(4x-1\right)'\left(2x+1\right)-\left(4x-1\right)\left(2x+1\right)'}{\left(2x+1\right)^2}\)
\(=\dfrac{4\left(2x+1\right)-2\left(4x-1\right)}{\left(2x+1\right)^2}=\dfrac{6}{\left(2x+1\right)^2}\)
a) \(y' = 2.3{{\rm{x}}^2} - \frac{1}{2}.2{\rm{x}} + 4.1 - 0 = 6{{\rm{x}}^2} - x + 4\).
b) \(y' = \frac{{{{\left( { - 2{\rm{x}} + 3} \right)}^\prime }.\left( {{\rm{x}} - 4} \right) - \left( { - 2{\rm{x}} + 3} \right).{{\left( {{\rm{x}} - 4} \right)}^\prime }}}{{{{\left( {{\rm{x}} - 4} \right)}^2}}}\)
\( = \frac{{ - 2\left( {{\rm{x}} - 4} \right) - \left( { - 2{\rm{x}} + 3} \right).1}}{{{{\left( {{\rm{x}} - 4} \right)}^2}}}\)
\( = \frac{{ - 2{\rm{x}} + 8 + 2{\rm{x}} - 3}}{{{{\left( {{\rm{x}} - 4} \right)}^2}}} = \frac{5}{{{{\left( {{\rm{x}} - 4} \right)}^2}}}\)
c) \(y' = \frac{{{{\left( {{x^2} - 2{\rm{x}} + 3} \right)}^\prime }\left( {{\rm{x}} - 1} \right) - \left( {{x^2} - 2{\rm{x}} + 3} \right){{\left( {{\rm{x}} - 1} \right)}^\prime }}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\)
\( = \frac{{\left( {2{\rm{x}} - 2} \right)\left( {{\rm{x}} - 1} \right) - \left( {{x^2} - 2{\rm{x}} + 3} \right).1}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\) \( = \frac{{2{{\rm{x}}^2} - 2{\rm{x}} - 2{\rm{x}} + 2 - {x^2} + 2{\rm{x}} - 3}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\)
\( = \frac{{{x^2} - 2{\rm{x}} - 1}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\)
d) \(y' = {\left( {\sqrt 5 .\sqrt x } \right)^\prime } = \sqrt 5 .\frac{1}{{2\sqrt x }} = \frac{{\sqrt 5 }}{{2\sqrt x }} = \frac{5}{{2\sqrt {5x} }}\).
tham khảo:
a)\(y'=\dfrac{\left(2\right)\left(x+2\right)-\left(2x-1\right)\left(1\right)}{\left(x+2\right)^2}\)
\(y'=\dfrac{5}{\left(x+2\right)^2}\)
b)\(y'=\dfrac{\left(2\right)\left(x^2+1\right)-\left(2x\right)\left(2x\right)}{\left(x^2+1\right)^2}\)
\(y'=\dfrac{2\left(1-x^2\right)}{\left(x^2+1\right)^2}\)
\(a,y'=\left(\dfrac{\sqrt{x}}{x+1}\right)'\\ =\dfrac{\left(\sqrt{x}\right)'\left(x+1\right)-\sqrt{x}\left(x+1\right)}{\left(x+1\right)^2}\\ =\dfrac{\dfrac{x+1}{2\sqrt{x}}-\sqrt{x}}{\left(x+1\right)^2}\\ =\dfrac{x+1-2x}{2\sqrt{x}\left(x+1\right)^2}\\ =\dfrac{-x+1}{2\sqrt{x}\left(x+1\right)^2}\)
\(b,y'=\left(\sqrt{x}+1\right)'\left(x^2+2\right)+\left(\sqrt{x}+1\right)\left(x^2+2\right)'\\ =\dfrac{x^2+2}{2\sqrt{x}}+\left(\sqrt{x}+1\right)\cdot2x\)
1. \(y'=3x^2\sqrt{x}+\dfrac{x^3-5}{2\sqrt{x}}=\dfrac{7x^3-5}{2\sqrt{x}}\)
2. \(y'=3x^5+\dfrac{3}{x^2}+\dfrac{1}{\sqrt{x}}\)
3. \(y'=2-\dfrac{2}{\left(x-2\right)^2}\)
\(y=\left(\frac{2}{3}\right)^x-\left(\frac{1}{6}\right)^x\Rightarrow y'=\frac{1}{x\ln\frac{2}{3}}+\frac{1}{x\ln6}\)
\(=\frac{2\ln2}{x\ln6\left(\ln2-\ln3\right)}\)